2004
DOI: 10.1038/sj.sc.3101702
|View full text |Cite
|
Sign up to set email alerts
|

Pain following spinal cord injury: the impact on community reintegration

Abstract: Study design: Prospective, correlational. Objectives: (1) Describe how pain changes over recovery from admission to spinal cord injury (SCI) rehabilitation, discharge and after 6 months of community living and (2) examine the relationship between pain and community integration at 6 months of community living. Setting: Tertiary rehabilitation centre, SCI unit, Vancouver, Canada. Methods: Subjects from 66 consecutive admissions to the SCI Program of a tertiary rehabilitation centre for the treatment of a traumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 23 publications
0
53
0
Order By: Relevance
“…14 Another factor could be psycho-social stresses. 10 Pain in the back and chest was seen in all the groups especially in the group that were 1-o6 months after injury. As stated earlier, the majority of subjects in the study fell into this age group.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…14 Another factor could be psycho-social stresses. 10 Pain in the back and chest was seen in all the groups especially in the group that were 1-o6 months after injury. As stated earlier, the majority of subjects in the study fell into this age group.…”
Section: Discussionmentioning
confidence: 88%
“…Pain impact and pain intensity were related to community reintegration. 10 As there has been no structured nationwide study reporting this aspect in India, the prevalence of this problem in India is unclear. There is a need to understand the effect of demographics on pain, so that preventive measures can be taken before its occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter pain has proven to be of high importance in the post-hospital stages of the rehabilitation process. 15 For the parameter 'sleep' it can be stated that it is clearly influenced by the parameter's pain and emotion. Insofar this parameter can be abandoned from a quality scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…2,1,[3][4][5][6][7] Other studies focus on the importance of related symptoms such as pain, psychosocial problems and loss of energy in the rehabilitation patient or the compliance of the patient is seen as a main outcome factor. [8][9][10][11][12][13][14][15][16][17] Studies researching the social reintegration mainly focus on occupational situation, living conditions and quality of life. [18][19][20][21][22][23][24] A multi-dimensionally measuring test device, internationally usable and applicable for inpatients as well as outpatients is thereby currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Kennedy et al 6 found that 25-45% of people with SCI experience persistent pain. In one study 27% of the 86% of participants who reported pain found it to negatively impact on activity participation 7,8 and have a negative impact on psychological affect and activities in daily living.…”
Section: Introductionmentioning
confidence: 99%